1996
DOI: 10.1139/v96-269
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrofurans from α-diazoketones due to facile ring opening – cyclization of donor–acceptor cyclopropane intermediates

Abstract: A series of a-diazoketones, 8, 25,28,31, and 34, have been synthesized and their reaction with ethyl vinyl ether examined under various reaction conditions. In the presence of metal salts (Rh,(OAc),, Pd(OAc),, CuC1) the ethoxydihydrofurans 12,37,39,41, and 43 are produced. Sensitized irradiation of the a-diazoketone 8 afforded the dihydrofuran 12 plus cyclobutanone 7, while direct photolysis of a-diazoketones 8,25,28,31, and 34 gave the cyclobutanones 7,38,40,42, and 44, respectively. A sample of the cycloprop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

1997
1997
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…For instance, metal-catalyzed reactions of cyclic diazoketones 326 with ethyl vinyl ether afforded dihydrofurans 328 with fair efficiency (Scheme ). In one case, the intermediate cyclopropyl ketone 327 was isolated and its smooth rearrangement to the dihydrofuran was demonstrated, suggesting that D−A cyclopropanes are generally intermediates in these formal [3 + 2] cycloadditions . This may also be the case in a related synthesis of fluoroalkyl-substituted dihydrofuran derivatives …”
Section: E D−a Cyclopropanes As Transient Intermediates1 (Formal) Per...mentioning
confidence: 89%
See 1 more Smart Citation
“…For instance, metal-catalyzed reactions of cyclic diazoketones 326 with ethyl vinyl ether afforded dihydrofurans 328 with fair efficiency (Scheme ). In one case, the intermediate cyclopropyl ketone 327 was isolated and its smooth rearrangement to the dihydrofuran was demonstrated, suggesting that D−A cyclopropanes are generally intermediates in these formal [3 + 2] cycloadditions . This may also be the case in a related synthesis of fluoroalkyl-substituted dihydrofuran derivatives …”
Section: E D−a Cyclopropanes As Transient Intermediates1 (Formal) Per...mentioning
confidence: 89%
“…In one case, the intermediate cyclopropyl ketone 327 was isolated and its smooth rearrangement to the dihydrofuran was demonstrated, suggesting that D-A cyclopropanes are generally intermediates in these formal [3 + 2] cycloadditions. 147 This may also be the case in a related synthesis of fluoroalkyl-substituted dihydrofuran derivatives. 148 An interesting route to 1,4-disubstituted furans employed Baylis-Hillman products 329 as starting materials, which were converted into dihydrofurans 331 via cyclopropyl ketones 330 (Scheme 92).…”
Section: (Formal) Pericyclic Reactionsmentioning
confidence: 92%
“…This is due to the ring strain causing, in turn, weaker conjugation of the diazo function (or the resulting carbene center) to the carbonyl group . The reactivity of such diazo compounds is illustrated by the reported involvement of α‐diazo γ‐butyrolactones and α‐diazo cyclopentanones in such classic transition metal‐catalyzed reactions as cyclopropanation,, cyclopropenation, X–H insertion and 1,3‐dipolar cycloaddition (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…An optimal example would be the Staudinger reaction, namely the acylation of imines by ketenes to form β-lactams, involving only aprotic starting materials. , Our approach to making this reaction catalytic for the first time involves using a much less nucleophilic imine through attachment of electron-withdrawing groups onto the imine nitrogen and α to the imine unit. We determined that electron-deficient α-imino ester 7 does not react with diphenylketene 8 18a at room temperature. However, we found that 5 mol % of 1d catalyzes the addition of 7 to 8 to afford β-lactam 10 in 85% yield after only 5 min in BTF at room temperature (Scheme ) 18b…”
mentioning
confidence: 99%
“…We determined that electron-deficient α-imino ester 7 does not react with diphenylketene 8 18a at room temperature. However, we found that 5 mol % of 1d catalyzes the addition of 7 to 8 to afford β-lactam 10 in 85% yield after only 5 min in BTF at room temperature (Scheme ) 18b 3 …”
mentioning
confidence: 99%